The Role of Salesforce CRM in Enhancing Customer Support and Service Operations - Sanodia, Geetesh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This comprehensive study examines the pivotal role of Salesforce Customer Relationship Management (CRM) in revolutionizing customer support and service operations. The research delves into Salesforce CRM's advanced features, integration capabilities, data analytics functionalities, and their impact on key performance metrics. By analysing its effects on agent productivity, mobile capabilities, security measures, and implementation challenges, this paper provides a holistic view of Salesforce CRM's contribution to the customer service landscape. The study also explores future trends, ethical considerations, and comparative analyses, offering valuable insights for organizations seeking to optimize their customer support strategies.